Magma degassing and intermittent lava dome growth - Taisne, B. (2012)
After its 1980 explosive eruption, Mount St Helens developed a lava dome that grew intermittently for several years. Each growth episode was followed by a long repose, suggesting that the magma column above the reservoir was in hydrostatic equilibrium. A mechanism allowing an increasingly thicker dome is proposed. Loading of the crater floor by the dome acts to prevent gas leakage from magma by closing fractures around the volcanic conduit. Fractures get closed down to a depth that increases as the dome grows. Calculations of dome thickness as a function of dome radius are in good agreement with observations. Renewed growth is triggered by the spreading of the dome. Gas retention over a larger depth extent allows smaller magma densities and a taller magma column above the reservoir. According to this model, small domes can in fact promote explosive volcanic conditions and be unstable